2017
DOI: 10.1016/j.quaint.2017.03.064
|View full text |Cite
|
Sign up to set email alerts
|

Records of East Asian monsoon activities in Northeastern China since 15.6 ka, based on grain size analysis of peaty sediments in the Changbai Mountains

Abstract: Peatlands provide a widespread terrestrial archive for Holocene study. However, little is known about the grain-size characteristics of peaty sediments and their environmental significance. In order to study these phenomena in detail, two sections from the Hani and Gushantun peatlands in the Changbai Mountain Area were cored and sub-sampled. Based on reliable calibrated AMS 14 C ages, we established grain size variations in the peat cores since 15.6 ka cal. BP. Our results showed that the peaty sediments in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 57 publications
6
38
0
Order By: Relevance
“…Summer insolation was highest during the early Holocene and decreased since then (Berger and Loutre, 1991). Indeed, there are other records from the region that indicate a wet early Holocene and dry late Holocene (Li et al, 2017), more in-line with the expected evolution of the EASM based on the local insolation. The contrasting response recorded in different proxies and in different regions indicates that the climatic evolution of NE China and especially the EASM across the Holocene remains poorly constrained.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Summer insolation was highest during the early Holocene and decreased since then (Berger and Loutre, 1991). Indeed, there are other records from the region that indicate a wet early Holocene and dry late Holocene (Li et al, 2017), more in-line with the expected evolution of the EASM based on the local insolation. The contrasting response recorded in different proxies and in different regions indicates that the climatic evolution of NE China and especially the EASM across the Holocene remains poorly constrained.…”
Section: Introductionsupporting
confidence: 60%
“…However, biomarker records are currently lacking from other peats in NE China that span the deglaciation such as the Gushantun peat deposits. Although pollen and grain sizes have been used to reconstruct Holocene climate and vegetation changes in the Gushantun peat (Liu et al, 1989;Zhao et al, 2015;Li et al, 2017), the temperature and paleohydrological variations in this peatland during the Holocene are currently unknown. To provide new information on the paleoclimate history of NE China, and dynamics of the EASM, our study employs high temporal resolution (~100-200 year resolution) paleoclimatic proxies based on the abundance and distribution of GDGTs, similar to that of previous Holocene studies (Zheng et al, 2014(Zheng et al, , 2015(Zheng et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…With relatively high temporal resolution, its humification, elemental content, organic content, pollen content, stable isotopes and more are all effective paleoclimate proxies, and are useful for studying past climate changes (Gorham, 1991). In China, many peatlands have been used to reconstruct climate changes across different time scales (Xiao et al, 2004;Hong et al, 2003Hong et al, , 2005Hong et al, , 2009Zhou et al, 2010;Lu et al, 2013;Chen et al, 2015;Liu et al, 2015;Zhao et al, 2017;Lei et al, 2017;Li et al, 2017;Xu et al, 2006;Ferret et al, 2012;Zheng et al, 2018). These have greatly improved our understanding of the dynamics of the EASM.…”
mentioning
confidence: 99%
“…Hani peatland in Jilin Province of northeast China is one of the few peatlands that remain wellpreserved (C. Schroder et al, 2007). It is situated at the frontal area of the EASM and previous studies have shown that past environmental changes can be reconstructed from pollen, grain size, stable isotopes as well as elemental and organic indicators (Ficken et al, 2000;Zhou et al, 2010;Hong et al, 2005Hong et al, , 2009Hong et al, 2010;Seki et al, 2009;McClymont et al, 2010;Yamamoto et al, 2010;Zheng et al, 2010Zheng et al, , 2011aZheng et al, , b, 2017Zheng et al, , 2018Huang et al, 2013;Wu et al, 2016;Li et al, 2017;Xiao et al, 2017), but its development history, and regional hydrology due to climate changes can still be further elaborated. For example, some records suggest that the precipitation in Hani decreased from the early to late Holocene (Hong et al, 2010;Hong et al, 2009Hong et al, , 2010 while some others suggest it increased gradually (Zheng et al, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation